Development of Tlogo Village Community Health - Yulia Ratimiasih; Bertika Kusuma Prastiwi; Fajar Ari Widiyatmoko; Dani Slamet Pratama; Buyung Kusumawardhana; Setiyawan Setiyawan; Maftukin Hudah (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This activity aims to provide health guidance to the Tlogo Village Community, Tuntang District, Semarang Regency by providing assistance with children's growth and development (posyandu), providing knowledge dissemination for teenagers who are still lacking in promiscuity and providing aerobic exercise training guidance to the community. This activity is carried out because many parents do not pay enough attention to their children's growth and development, so posyandu, youth care, health care and low levels of exercise have the potential to reduce the level of public health. Assistance from the PKM University of PGRI Semarang (UPGRIS) Team uses lecture and demonstration methods. The expected output is increased knowledge of parents in paying attention to children's growth and development, increased knowledge of teenagers in free association, and community skills among teenagers. There is also a lot of community participation in aerobic exercise. The result of this service is increased community knowledge and skills regarding health. This good habit needs to be improved in the future with better programs.